Sistem Pengelolaan Bantuan Langsung Tunai Berbasis Radio Frequency Identification (RFID) - Sarimuddin Sarimuddin (STMIK Pringsewu, 2023)
Direct cash assistance is a government assistance program in the form of cash or other assistance, both conditional and unconditional. BLT receipts in the village of Bonemarambe were made at the village office by bringing an identity card (KTP) as proof of receipt. However, in general, the beneficiary community does not receive it directly but is represented by family, relatives or others. This is a problem because errors often occur in the distribution of assistance. There was a factor of mistaken identity when registering the beneficiary, which resulted in the aid distribution not being up to par and sometimes one of the residents received a help 2 (twice) times in the same period. This study aims to use information technology in the form of use of radio frequency identification devices (RFID) to manage direct cash assistance (BLT) in the village of Bonemarambe. where the tool performance system is that each aid recipient has a responder tag that will later be used as a BLT ID card. To enable BLT receipts to be effective, efficient and of course targeted. this is proven by being able to discriminate between people who have received help and people who have not received help at a certain time.